Integration Model of Nutritional Education, Tuina Massage and Psychomotoric Training (Gina Latrik) in Efforts for Food Security and Decreasing of Stunting in Toddler at UPT Puskesmas Klungkung I - Juniarsana, I Wayan; Sukraniti, Desak Putu; Suriani, Ni Luh; Ermayanti, Ni Gusti Ayu Manik (Tropical Plantation Journal, 2024)
Stunting is still a health problem faced by Indonesian children. The incidence of stunting according to Indonesian Nutrition Status Survey (SSGI) in 2021 was 24.4% and in 2022 itâ€™s decrease to 21.6%. There were exceeds from WHO recommended requirement 20%. Holistic efforts from the government and society were needed to accelerate stunting reduction.Â This research aims to produce an integrated approach model such as nutrition education, tuina massage and psychomotor training (Gina Latrik) in accelerating to decrease of stunting rates. This type of research is true experimental.Â Subjects were divided into two groups, ie;Â Â â€œGina Latrik Bâ€ treatment group (balanced nutrition education, massageÂ TuinaÂ therapy with a frequency of 3â€“5 times/week and psychomotor training) and control group â€œGina Latrik Aâ€ (balanced nutrition education, massage therapyTuinawith a frequency of 1â€“2 times/week and psychomotor training). The average knowledge level of toddler mothers after given the intervention was 83.66 Â± 4.04% in the control group and 87.98 Â± 5.88% in treatment group andÂ significant difference with p=0.040 (p0.05).Â The results of research on macronutrient intake (energy, protein) in two groups showed significant differences (p0.05) and nutrient intake in Gina Latrik B was better than Gina Latrik A. Nutritional status results with height/age shows that the Z score =Â 2.17 Â± 0.379 (Gina latrik A) dan 2.73 Â± 0.452Â for Gina Latrik B) with p=0.003 (p0.05), there was a significant difference on t-independent analysis. That means the Gina Latrik B was better than Gina Latrik A. Psychomotor development shows an increase in both groups, in Gina Latrik A there is an increase in psychomotor ability in the "appropriate" category of 33,30% to 60%. Meanwhile, in the Gina Latrik B group there was a sharp increase from 39.39% to 90.91%. Based on analysistÂ independent showed a significant difference p = 0.003 (p0.005). Based on the results it can be prove that Gina Latrik B intervention was better for decreasing of stunting compared to Gina Latrik A.